2008
DOI: 10.1093/rheumatology/ken264
|View full text |Cite
|
Sign up to set email alerts
|

The CO-releasing molecule CORM-2 is a novel regulator of the inflammatory process in osteoarthritic chondrocytes

Abstract: These data have opened new mechanisms of action for CORM-2, raising the prospect that CO-releasing molecules are an interesting strategy for the development of new treatments in articular conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 41 publications
5
22
0
1
Order By: Relevance
“…The antinociceptive and anti-inflammatory effects produced by substances that can liberate carbon monoxide during inflammatory diseases have previously been shown (Guillén et al, 2008;Negrete et al, 2014). In accordance, our results further demonstrated that the administration of CoPP (an HO-1 inducer) also inhibited the mechanical and thermal hypersensitivity induced by chronic peripheral inflammation in mice.…”
Section: Discussionsupporting
confidence: 90%
“…The antinociceptive and anti-inflammatory effects produced by substances that can liberate carbon monoxide during inflammatory diseases have previously been shown (Guillén et al, 2008;Negrete et al, 2014). In accordance, our results further demonstrated that the administration of CoPP (an HO-1 inducer) also inhibited the mechanical and thermal hypersensitivity induced by chronic peripheral inflammation in mice.…”
Section: Discussionsupporting
confidence: 90%
“…We have shown that these effects were not dependent on the inhibition of COX-2/mPGES-1 enzyme activity. Although the reduction in heme availability may result in COX-2 protein possessing a low activity, our recent data [41] suggest that a product of HO-1 activity such as CO may be responsible for the reductions in PGE 2 production after HO-1 induction. Our results Recently, we have reported that HO-1 protects against cartilage degradation through the inhibition of the expression of several matrix metalloproteinases [20].…”
Section: Discussionmentioning
confidence: 75%
“…Hervera et al showed that the administration of CORM-2 attenuated mechanical and thermal hypersensitivity in neuropathic pain stimulated by chronic constriction of sciatic nerve in mice [25]. Also, CORMs generated antinociceptive and anti-inflammatory effects in inflammatory diseases [49].…”
Section: Discussionmentioning
confidence: 99%